Development of a Delirium Risk Predication Model among ICU Patients in Oman - Rasha Khamis Al-Hoodar; Eilean Rathinasamy Lazarus; Omar Alomari; Omar Alzaabi (Anesthesiology Research and Practice)
Background. Delirium is a common disorder among patients admitted to intensive care units. Identification of the predicators of delirium is very important to improve the patient’s quality of life. Methods. This study was conducted in a prospective observational design to build a predictive model for delirium among ICU patients in Oman. A sample of 153 adult ICU patients from two main hospitals participated in the study. The Intensive Care Delirium Screening Checklist (ICDSC) was used to assess the participants for delirium twice daily. Result. The results showed that the incidence of delirium was 26.1%. Multiple logistic regression analysis showed that sepsis (odds ratio (OR) = 9.77; 95% confidence interval (CI) = 1.91–49.92; P<0.006), metabolic acidosis (odds ratio (OR) = 3.45; 95% confidence interval [CI] = 1.18–10.09; P=0.024), nasogastric tube use (odds ratio (OR) 9.74; 95% confidence interval (CI) = 3.48–27.30; P≤0.001), and APACHEII score (OR = 1.22; 95% CI = 1.09–1.37; P≤0.001) were predictors of delirium among ICU patients in Oman (R2=0.519, adjusted R2=0.519, P≤0.001). Conclusion. To prevent delirium in Omani hospitals, it is necessary to work on correcting those predictors and identifying other factors that had effects on delirium development. Designing of a prediction model may help on early delirium detection and implementation of preventative measures.